2012
DOI: 10.2139/ssrn.2135452
|View full text |Cite
|
Sign up to set email alerts
|

Trade Union Membership and Sickness Absence: Evidence from a Sick Pay Reform

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…With regard to the control variables (see Table in the ), the estimated coefficients are generally in line with results based on SOEP data (Goerke and Pannenberg ; Puhani and Sonderhof ; Ziebarth and Karlsson ) . When comparing the size of the estimated coefficients of the works council dummy across the different specifications depicted in Table , it can be observed that they decline by about a third (30 percent) in the incidence (duration) specification when including, for example, firm and industry characteristics.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…With regard to the control variables (see Table in the ), the estimated coefficients are generally in line with results based on SOEP data (Goerke and Pannenberg ; Puhani and Sonderhof ; Ziebarth and Karlsson ) . When comparing the size of the estimated coefficients of the works council dummy across the different specifications depicted in Table , it can be observed that they decline by about a third (30 percent) in the incidence (duration) specification when including, for example, firm and industry characteristics.…”
Section: Resultssupporting
confidence: 85%
“…Turning to the control variables, we take standard confounding factors into account (Goerke and Pannenberg ; Puhani and Sonderhof ; Ziebarth and Karlsson , ). Accordingly, we control for personal characteristics such as disability status, being female, marital status, living with a partner, being of foreign nationality, having a foreign background (immigrant), subjective general health status (good, bad), having children under the age of 14, age, educational attainment, satisfaction with current health status, and twelve regional dummies .…”
Section: Data and Empirical Specificationmentioning
confidence: 99%
“…Goerke and Pannenberg (2011), for example, show that trade union members in Western Germany are less likely to be dismissed individually than non-members. In addition, Goerke and Pannenberg (2015) estimate that union members take about a day more of sickness-related absence annually than non-members. This effect is quantitatively comparable to the estimated OLS-vacation differential between members and non-members.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to control for union membership, as several studies have shown that union workers are more absent‐prone than non‐union workers (Goerke and Pannenberg, ; Mastekaasa, ).…”
mentioning
confidence: 99%